TINJAUAN VIKTIMOLOGI TERHADAP KORBAN PENIPUAN UANG DALAM SISTEM PRE ORDER VOUCHER GAME ONLINE DALAM KASUS NOS GAMING - NIM. A1011171018, ILHAM AFANDI (Fakultas Hukum Universitas Tanjungpura, 2024)
AbstractVictimological review in the case of money fraud in the online game voucher pre-order system at NOS Gaming consists of two aspects, namely the active and passive roles of the victims. Actively, victims do not exercise caution in their transactions, enticed by low promotional prices, and motivated by easy trust and a desire for significant profit. They engage in these transactions due to their interest in offers priced well below market rates and promises of exclusive rewards such as action figures. For instance, some victims reported being initially drawn in by enticing low prices.Passively, the role of victims relates to their trust in the modus operandi employed by NOS Gaming. Victims trust fake evidence presented by NOS Gaming, such as business permits (SIUP) and claims of legal businesses in sneakers and health products. NOS Gaming also utilizes testimonials related to crypto investments to bolster their image. The fraud is exacerbated by a Ponzi scheme where NOS Gaming exploits transaction system bugs to deceive victims. Victims believe NOS Gaming operates legitimately, when in reality, it serves as a facade to deceive them.The research problem addressed in this study is